Osobennosti podvedeniya edinobortsev k sostoyaniyu najvysshej gotovnosti - Sukhanov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The training of single combater at the stage of the profound perfection is more and more correlating to the year calendar of competitions. In the single combats, which are included in the program of Olympic games, for example, an emphasis makes on the four year cycle. Thus they put the purpose always: to show the best result at the main competition of year or four year cycle. It is possible to achieve it by the rational construction of the training both in the year cycle, and by the direct training for competitions. The author shows it on an example of the stage of the profound perfection in the year training. First of all, it is necessary to allocate the main and selection competitions of the year. This question strictly stipulates at the level of the federation. It is very important, how many days are between each other selection and main competitions of the year. All other competitions should be considered as bringing (preparatory), the sports result should not be the main thing for them. It is much more important the variety and quality of the single combat completing. The participation in the each competition, irrespective of its purpose, it is necessary to anticipate by special training and to finish with the serious state diagnosis and restoration of the athlete.